2022
DOI: 10.3390/diagnostics12040962
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Assessment of Congestion by Cardiovascular and Pulmonary Ultrasound and Biomarkers in Heart Failure

Abstract: Worsening chronic heart failure (HF) is responsible for recurrent hospitalization and increased mortality risk after discharge, irrespective to the ejection fraction. Symptoms and signs of pulmonary and systemic congestion are the most common cause for hospitalization of acute decompensated HF, as a consequence of increased cardiac filling pressures. The elevated cardiac filling pressures, also called hemodynamic congestion, may precede the occurrence of clinical congestion by days or weeks. Since HF patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…However, the decrease in IVC diameter and the increase in IVC collapsibility index were both correlated with the improvement of eGFR decline rate after treatment with SGLT2 inhibitors. Better fluid control during outpatient visits following the introduction of SGLT2 inhibitors was linked to central venous pressure decrease, which acted in a renal protective manner via improvement of renal congestion and may have induced the favorable effect on renal function in this study, although it is only our speculation because we did not directly assess renal congestion by examining intrarenal venous flow patterns or otherwise [42] .…”
Section: Discussionmentioning
confidence: 90%
“…However, the decrease in IVC diameter and the increase in IVC collapsibility index were both correlated with the improvement of eGFR decline rate after treatment with SGLT2 inhibitors. Better fluid control during outpatient visits following the introduction of SGLT2 inhibitors was linked to central venous pressure decrease, which acted in a renal protective manner via improvement of renal congestion and may have induced the favorable effect on renal function in this study, although it is only our speculation because we did not directly assess renal congestion by examining intrarenal venous flow patterns or otherwise [42] .…”
Section: Discussionmentioning
confidence: 90%
“…➢ RA volume (Single plane): Tracing the RA inner boundary omitting the area under the TV annulus from an apical 4 chamber view that contains the whole RA and was not foreshortened (dedicated right heart view) (8) . ➢ Systolic PAP (sPAP): by assessment of TR velocity & IVC size & collapsibility (9) .…”
Section: Methodsmentioning
confidence: 99%
“…Objective assessment of hemodynamic conditions is fundamental to guide the clinical management of the cardiac surgery patient during the postoperative period [ 1 , 2 , 3 ]. Meticulous fluid management is crucial in patients undergoing cardiac surgery, particularly in those with heart failure; prolonged operative and aortic cross-clamp time; or preexisting kidney, lung, or liver dysfunction [ 4 , 5 ]. Recent studies suggested that abdominal congestion can lead to or worsen renal and hepatic dysfunction and thus increase the risk of postoperative complications and lead to higher resource utilization [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%